Paediatric CT Dose Optimization in a General Hospital - Guerra, Vivian Heidorne; Nersissian, Denise Yanikian; Melo, Camila Souza; Vasconcellos, Caio; Freitas, Rebeca Gonçalves; Sawamura, Márcio; Gebrim, Eloisa; Costa, Paulo Roberto (Revista Brasileira de Física Médica, 2019)
This work presents a methodology for the optimization of protocols applied to pediatric patients who underwent brain and chest computed tomography examinations. The implementation of this methodology aims to reduce the dose of ionizing radiation delivered to patients and the consequent risk associated with radiation, without decreasing the diagnostic image quality. The comparison between the results of CTDIvol (computed tomography dose index) and DLP (dose-length product) dosimetric quantities before the optimization process and their corresponding results after the implementation of the optimization process was done through boxplot graphs. It is noteworthy that the implementation of this methodology allows reductions in the range between 18 and 50% of the dosimetric values evaluated in this study. In addition, the case of brain computed tomography scans, in which the cohort of the evaluated patients is larger, is a highlight, which should also reflect in the reduction of the absorbed radiation dose by this particularly important group of patients.